Loss‐of‐function variants in Kv11.1 cardiac channels as a biomarker for SUDEP. Issue 7 (18th May 2021) - Soh, Ming S.; Bagnall, Richard D.; Bennett, Mark F.; Bleakley, Lauren E.; Mohamed Syazwan, Erlina S.; Phillips, A. Marie; Chiam, Mathew D. F.; McKenzie, Chaseley E.; Hildebrand, Michael; Crompton, Douglas; Bahlo, Melanie; Semsarian, Christopher; et al.
Abstract: Objective: To compare the frequency and impact on the channel function of KCNH2 variants in SUDEP patients with epilepsy controls comprising patients older than 50 years, a group with low SUDEP risk, and establish loss‐of‐function KCNH2 variants as predictive biomarkers of SUDEP risk. Methods: We searched for KCNH2 variants with a minor allele frequency of <5%. Functional analysis in Xenopus laevis oocytes was performed for all KCNH2 variants identified. Results: KCNH2 variants were found in 11.1% (10/90) of SUDEP individuals compared to 6.0% (20/332) of epilepsy controls ( p  = 0.11). Loss‐of‐function KCNH2 variants, defined as causing >20% reduction in maximal amplitude, were observed in 8.9% (8/90) SUDEP patients compared to 3.3% (11/332) epilepsy controls suggesting about threefold enrichment (nominal p  = 0.04). KCNH2 variants that did not change channel function occurred at a similar frequency in SUDEP (2.2%; 2/90) and epilepsy control (2.7%; 9/332) cohorts ( p  > 0.99). Rare KCNH2 variants (<1% allele frequency) associated with greater loss of function and an ~11‐fold enrichment in the SUDEP cohort (nominal p  = 0.03). In silico tools were unable to predict the impact of a variant on function highlighting the need for electrophysiological analysis. Interpretation: These data show that loss‐of‐function KCNH2 variants are enriched in SUDEP patients when compared to an epilepsy population older than 50 years, suggesting that cardiac mechanisms contribute to SUDEP risk. We propose that genetic screening in combination with functional analysis can identify loss‐of‐function KCNH2 variants that could act as biomarkers of an individual's SUDEP risk.